Gerakan Sadar Wisata Di Desa Wisata Sempajaya - Tambunan, Sarah Rouli; Rismawati; Manurung, Jhon Sihar; Haro, Jamardua (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2022)
The concept of tourism awareness expects people to play the role of good hosts in their respective environments. In promoting tourism awareness, the Ministry of Tourism and Creative Economy will organize a tourism awareness campaign program in 65 tourism villages throughout 2022-2023. Compared to the number of tourist villages of 3416 villages, the number of tourist villages exposed to the campaign program is still minimal. Sempajaya Village, located in Berastagi district, Karo Regency, North Sumatra, is one of the tourist villages registered with the Ministry of Tourism and Creative Economy. This village has tourism potential, such as cultural tourism, nature tourism, and agrotourism. Although the tourism potential is significant, the knowledge of the people of Sempajaya village about tourism is still low, so the existing tourism potential cannot be developed properly. The community is also considered less friendly, and minimal in maintaining cleanliness. In response to this condition, the Polmed service team initiated to increase tourism awareness of the people of Sempajaya Village through tourism awareness training Sapta Pesona training, CHSE (Clean, Health, Safety, Environment), and excellent service. Furthermore, billboards will also be made containing messages of sapta pesona and flower plants to support the beauty of the village as part of sapta pesona. Konsep sadar wisata mengharapkan masyarakat untuk berperan sebagai tuan rumah yang baik di lingkungannya masing-masing. Dalam menggalakkan sadar wisata, Kemenparekraf menyelenggarakan program kampanye sadar wisata di 65 desa wisata sepanjang tahun 2022-2023. Jika dibandingkan dengan jumlah desa wisata sebesar 3416 desa, maka jumlah desa wisata yang terpapar program kampanye masih sangat sedikit. Desa Sempajaya yang terletak di kecamatan Berastagi, Kabupaten Karo Sumatera Utara merupakan salah satu desa wisata yang terdaftar di Kemenparekraf, Desa ini memiliki potensi wisata seperti wisata budaya, wisata alam dan agrowisata. Walaupun potensi pariwisatanya besar, tingkat pengetahuan masyarakat desa Sempajaya akan pariwisata masih rendah sehingga potensi pariwisata yang ada belum dapat dikembangkan dengan baik. Masyarakat juga dianggap kurang ramah, minim dalam menjaga kebersihan. Merespon kondisi ini, tim pengabdian Polmed beriniasi untuk meningkatkan sadar wisata masyarakat Desa Sempajaya melalui pelatihan sadar wisata yaitu: pelatihan Sapta Pesona, CHSE ( Clean, Health, Safety, Environment ), dan pelayanan prima. Lebih lanjut juga akan dibuatkan baliho berisi pesan sapta pesona dan tanaman bunga untuk mendukung keasrian desa sebagai bagian sapta pesona.